Tindak Pidana Plagiarisme terhadap Novel Elektronik pada Aplikasi Wattpad - Ni Wayan Nita Dewi; I Nyoman Gede Sugiartha; I Wayan Arthanaya (Jurnal Interpretasi Hukum, 2022)
Plagiarism is taking a work, statement, and so on from someone else and making it like their own work and statement. The perpetrators of plagiarism are called plagiarists because there are many ordinary people who violate other people's copyrighted works on the Wattpad digital application. Publishing literary works by the general public and making them easier to read in the application does not rule out copyright infringement. The purpose of this research is to analyze the legal arrangements for the crime of plagiarism and what are the legal protections for victims whose electronic novels are plagiarized on the Wattpad application. The sources of legal materials for this research consist of primary, secondary and tertiary materials. Primary materials are sourced from laws and regulations which are the basis for analyzing problems. Then secondary legal materials come from legal books and journals that support primary sources. While tertiary materials are sourced from other reading materials on the website. Data collection techniques used are library techniques, identifying, and analyzing materials. The result shows that plagiarism can be a criminal act for stealing other people's copyrights. In Indonesia, copyright issues are regulated in the Copyright Law, Number 28 of 2014. Copyright law includes provisions of criminal law that can be sanctioned to anyone who violates the rights copyright for other people's creations.